Exploiting silver trifluoromethanesulfonate as efficient and reusable catalyst for the synthesis of dihydropyrimidine derivatives under different reaction environments. (2nd October 2019) - Roy, Dipak Kumar; Tamuli, Kashyap Jyoti; Bordoloi, Manobjyoti
Abstract: Different results were generated under different reaction conditions for the multicomponent reactions. Herein, an efficiently improved and mild protocol for the synthesis of dihydropyrimidine derivatives using cheap silver trifluoromethanesulfonate (CF3 SO3 Ag) as reusable catalyst is explained. With conventional heating and microwave irradiation method, the synthesis of substituted 3, 4‐dihydropyrimidine‐2(1 H )‐one and 3, 4‐dihydropyrimidine‐2(1 H )‐thione was achieved in different solvent environments like acetonitrile, water, and under solvent free neat condition. Moreover, the solvents (CH3 CN and H2 O) containing the CF3 SO3 Ag were reused for several times without loss of much catalytic activity after separation from the desired products. Thus, the method provides much improved and efficient alternative pathway to the original Biginelli reaction. Abstract :